2020
DOI: 10.1017/s0144686x20000082
|View full text |Cite
|
Sign up to set email alerts
|

A state-of-the-art review of the socio-ecological correlates of volunteerism among older adults

Abstract: The health and social benefits of volunteering behaviours by older adults are well acknowledged. However, few review articles have been concerned with the correlates/dimensions of older adults’ volunteerism. Some focused only on the North American context or reviewed studies only up to 2008. This study reviewed the recent global literature in the past decade about the correlates of older adults’ volunteerism. We carried out a literature search in PsycINFO, Social Services Abstracts, Sociological Abstracts and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 59 publications
(137 reference statements)
0
13
0
Order By: Relevance
“…For example, the effect of employment on volunteering may be influenced by life stage, such that those experiencing work-retirement transitions may be more involved in volunteering than non-retired populations 100 , and other new roles in later life (e.g., caregiving) may influence later life volunteering 67 . Future work will need to continue to investigate factors at the micro-, meso-, and macro-levels that predict volunteering specifically in older populations, predictors of volunteering across the lifespan, and predictors that may be more or less salient at different points during the life course 34 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the effect of employment on volunteering may be influenced by life stage, such that those experiencing work-retirement transitions may be more involved in volunteering than non-retired populations 100 , and other new roles in later life (e.g., caregiving) may influence later life volunteering 67 . Future work will need to continue to investigate factors at the micro-, meso-, and macro-levels that predict volunteering specifically in older populations, predictors of volunteering across the lifespan, and predictors that may be more or less salient at different points during the life course 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, prior studies assessing predictors of volunteering have assessed micro-level contributors (incentive factors) and inhibitors (obstructive factors) of volunteering at the individual level in several key domains (health-related, psychological, etc. ), creating a strong foundation for us to now assess how changes in these individual-level factors are associated with subsequent volunteering 34 . Future studies should further investigate other potential predictors (e.g., meso- and macro-level factors, factors available outside of HRS, etc.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we adopted the socioecological and person-in-environment frameworks, which emphasize how interactions with environments such as home and community can shape the health and social behaviors of older adults, such as community social cohesion, sense of belonging, and civic engagement (Lu et al, 2021). The conceptual frameworks suggest accounting for multilevel factors (Bengston & Settersten, 2016), such as individual (age, gender, living arrangements), home (design, space), and community (cohesion, access to service, safety) factors, in understanding the relationships among person, place, environments, and assessment of health.…”
Section: Srh and Home And Community Environmentsmentioning
confidence: 99%
“…This programme not only improves physical health but also improves social contact among older persons. Numerous studies have shown how important it is to create inclusive and accessible outdoor environments, such as senior playgrounds, parks and meeting areas to encourage social participation and a healthy lifestyle [33], [31], [34], [24]. Aside from that, the country's ageing population has become the primary consumer, with purchasing power over the majority of goods and services [20].…”
Section: Goal 11: Sustainable Cities and Communitiesmentioning
confidence: 99%